Focus on Semaglutide 2.4 mg/week for the Treatment of Metabolic Dysfunction‐Associated Steatohepatitis - Petta, Salvatore (2025)
Semaglutide has recently received conditional accelerated approval in the US for treatment of metabolic dysfunction-associated steatohepatitis (MASH) with significant or advanced liver fibrosis (stage F2/F3). Phase 2 and 3 clinical trials show that subcutaneous semaglutide 2.4 mg/week leads to significant improvements in hepatic steatosis, disease activity, resolution of MASH and reduction in liver fibrosis. These benefits parallel weight loss and are accompanied by improved metabolic outcomes, including better glucose control and lipid profiles, as well as consistent benefits for cardiovascular and renal health. The treatment's safety profile is manageable, with gastrointestinal issues being the most frequent side effects, and no new safety concerns have been identified. Data on long-term tolerability, treatment retention and clinical events are now awaited in people with MASH fibrosis. The evidence regarding semaglutide's ability to directly target the liver and improve liver damage in cirrhosis, and its impact on muscle mass in at-risk populations, remains limited. Thus, in patients with advanced disease, it should be viewed primarily as a therapy that modifies metabolic disease. Practically, semaglutide is most suitable as a first-line treatment to prevent liver complications for people with MASH and stage F2/F3 fibrosis with severe metabolic dysfunction, obesity, or type 2 diabetes who could benefit from both liver and cardiovascular-renal improvements. Treatment should be tailoured to each individual, with ongoing monitoring of body weight, serum aminotransferase levels and direct measurement of liver fat and stiffness to guide therapy.